POTENSI DAYA SAING PETERNAKAN RAKYAT SAPI POTONG DI PROVINSI KALIMANTAN TENGAH BAGIAN BARAT - Firdaus Husein; Monasdir Monasdir; Erlina Astuti; Donatalia Desi Hadu; Florida Sina (Program Studi Agribisnis Fakultas Pertanian, 2025)
ABSTRACT Beef cattle farming plays a vital role in national meat supply and regional economic development. The western region of Central Kalimantan, comprising Kotawaringin Barat, Lamandau, and Sukamara Regencies, holds substantial potential for the development of this sector due to its abundant land and feed resources. This study aims to analyze the competitive and comparative advantages of beef cattle farming using the Policy Analysis Matrix (PAM) approach. The research was conducted from January to March 2025 using a census method involving 45 farmers (15 farmers per regency) with a minimum herd size of 15 head. Data collected included production costs, revenues, input–output prices, and policy factors influencing the farming system. The PAM analysis was employed to assess competitive advantage (Private Cost Ratio/PCR) and comparative advantage (Domestic Resource Cost Ratio/DRCR), as well as the impact of policy on profitability. The results showed that beef cattle farming in the western region of Central Kalimantan possesses a competitive advantage, with a PCR value of 0.65, and a comparative advantage, with a DRCR value of 0.58, indicating efficiency both financially and economically. Government support in the form of local feed subsidies and cattle vaccination programs has enhanced profitability, although price distortions remain for certain production inputs. Optimizing oil palm–cattle integration, improving feed quality, and strengthening market access were identified as key strategies to further enhance competitiveness in the future.